Internações por condições sensíveis à atenção primária à saúde por hipertensão e diabetes no estado de Minas Gerais - Silva, Siméia Soares Pereira da (2024)
Chronic Non-Communicable Diseases (NCDs), such as Diabetes Mellitus (DM) and Systemic Arterial Hypertension (SAH), represent important causes of morbidity and mortality and have a high prevalence in Brazil. These conditions are recognized as sensitive to Primary Health Care (PHC) interventions and are often used as indicators for evaluating the effectiveness of health services, through the analysis of Hospitalizations for Ambulatory Care-Sensitive Conditions (ACSC). The objective of this study was to perform an analysis of the temporal trend of HACSC due to SAH and DM in the period from 2012 to 2022, in Minas Gerais. This is an ecological study of temporal trend, conducted with data from the state of Minas Gerais, in the period from 2012 to 2022. Information on hospitalizations for hypertension and DM was collected from the Hospital Information System of the Unified Health System (SIHSUS). The variables analyzed included gender, age group, and race/color. HACSC rates were calculated based on the population estimated by the Brazilian Institute of Geography and Statistics (IBGE), and were expressed per 100,000 inhabitants. The trend analysis of the historical series was performed by generalized linear regression using the Prais-Winsten method. In general, the findings of this study indicated a reduction in hospitalizations for hypertension and DM over the years. The highest rates of HACSC due to hypertension and DM were observed among individuals of advanced age and of yellow race/color. Regarding gender, there was a higher frequency of hospitalizations for hypertension among men and for DM among women until 2016, while from 2019 to 2022 hospitalizations for DM were more prevalent in men. Although there may have been advances in access to and quality of PHC, as indicated by the possible overall reduction in HACSC, the specific data on SAH and DM point to the need for greater attention to these conditions. The need for public policies that integrate intersectoral strategies to address the social determinants of health and promote better long-term health outcomes is highlighted.